Impact of COVID-19 on the international tourism demand in Peru. An application of the Box-Jenkins methodology - Tudela, Juan Walter (2022)
In recent years, tourism has taken on considerable importance as a factor of economic and social development in the world, contributing not only to the economic growth of developing countries, but also to the improvement of the quality of life of the people involved in the sector. However, given the global health crisis caused by the coronavirus (COVID-19), the tourism sector was one of the most affected sectors due to the various public safety policies adopted by different countries in the world, especially by European countries that account for more than 50% of international tourism in the Americas, Africa, and the Middle East. The objective of this research was to estimate and project international tourism demand in Peru with monthly time series data from January 2003 to December 2020 through a seasonal ARIMA process proposed by Box-Jenkins called SARIMA. The results show that the seasonal ARIMA model (1,1,1)(0,1,1,1)12 was appropriate for the projection given the Akaike (AIC) and Schwarz (SC) criteria. The model estimates a parsimonious cyclical recovery of international tourist arrivals to our country; however, the evolution of COVID-19 in public health maintains uncertainty about new challenges in the tourism sector that would allow its sustainability and resilience over time. Immediate fiscal and monetary measures are urgently needed to safeguard employment and survival mechanisms for businesses.